2012
DOI: 10.1007/s00707-011-0611-y
|View full text |Cite
|
Sign up to set email alerts
|

Pyroelectric and pyromagnetic coefficients of functionally graded multilayered multiferroic composites

Abstract: This paper presents a method for analyzing some product properties of functionally graded magnetoelectro-thermoelastic (METE) multilayer composites. The method is based on an exact matrix formulation for the effective properties of multilayer composites with various coupled physical effects including piezoelectricity, piezomagnetism, and thermoelasticity. Analytical expressions are derived for the effective properties of a functionally graded transversely isotropic METE multilayer composite. The effects of fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…There is a mechanical coupling between the magnetostrictive phase and piezoelectric phase [9,10]. The ME composites prepared by combining such phases in proper molar proportions have been observed to yield higher ME output as compared to single phase compounds and seem to be quite promising from an application point of view such as in large area magnetic field sensors and four state memory devices [11]. In the context of piezoelectric-magnetostrictive composites, the so-called product property [2] shows a nonlinear magnetoelectric (ME) effect which makes it difficult to use in linear devices.…”
Section: Introductionmentioning
confidence: 99%
“…There is a mechanical coupling between the magnetostrictive phase and piezoelectric phase [9,10]. The ME composites prepared by combining such phases in proper molar proportions have been observed to yield higher ME output as compared to single phase compounds and seem to be quite promising from an application point of view such as in large area magnetic field sensors and four state memory devices [11]. In the context of piezoelectric-magnetostrictive composites, the so-called product property [2] shows a nonlinear magnetoelectric (ME) effect which makes it difficult to use in linear devices.…”
Section: Introductionmentioning
confidence: 99%
“…The poling direction of both materials is oriented in the x 3 -direction. It should be mentioned that the pyromagnetic constant of the CoFe 2 O 4 is not available in the literature and some authors chose it to be equal to zero, see Tang and Yu (2009), Challagulla and Georgiades (2011), and Kim et al (2012), for example. In this article, the value of the slope of the magnetic flux with respect to temperature d B /d θ = 0.01 T/K has been determined from Figure 9 of Naiden et al (2008) at room temperature.…”
Section: Applicationsmentioning
confidence: 99%
“…Tey showed that the sheet's vertical and transverse shear stresses could be studied as degrees of freedom by considering the mechanical deformation components and electrical and magnetic potentials. Using Lord-Schulman's theory to analyze the electro-magneto-thermoplastic response of thermoplastic magneto-electro-elastic (TMEE), a hollow cylinder made of magneto-electro-elastic (MEE) functionally graded material was used by Abbas and Zenkour [32] to study the efect of comfort time, temperature, and volume fraction of each phase on the static parameters of a smart-graded hollow cylinder. Tis study is presented as a guide for the Termoelastic magneto-electro-elastic (TMEE) response of smart materials under the heat source infuence.…”
Section: Introductionmentioning
confidence: 99%